2018
DOI: 10.3390/ijms19082276
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis Heat Stress-Induced Proteins Are Enriched in Electrostatically Charged Amino Acids and Intrinsically Disordered Regions

Abstract: Comparison of the proteins of thermophilic, mesophilic, and psychrophilic prokaryotes has revealed several features characteristic to proteins adapted to high temperatures, which increase their thermostability. These characteristics include a profusion of disulfide bonds, salt bridges, hydrogen bonds, and hydrophobic interactions, and a depletion in intrinsically disordered regions. It is unclear, however, whether such differences can also be observed in eukaryotic proteins or when comparing proteins that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…In plants the genomic-wide information available regarding IDPs is rather limited in comparison to other eukaryotic organisms and it is circumscribed to Arabidopsis thaliana [10,11], and a few other plant models [12,13,14]. The fact that many IDPs can serve as signal integrators in signaling cascades and stress-response processes, allows the supposition that their role can be especially important in plant development and adaptation to environmental conditions, probably by providing them with a fast mechanism to obtain complex and highly interconnected molecular networks [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In plants the genomic-wide information available regarding IDPs is rather limited in comparison to other eukaryotic organisms and it is circumscribed to Arabidopsis thaliana [10,11], and a few other plant models [12,13,14]. The fact that many IDPs can serve as signal integrators in signaling cascades and stress-response processes, allows the supposition that their role can be especially important in plant development and adaptation to environmental conditions, probably by providing them with a fast mechanism to obtain complex and highly interconnected molecular networks [15].…”
Section: Introductionmentioning
confidence: 99%
“…The fact that many IDPs can serve as signal integrators in signaling cascades and stress-response processes, allows the supposition that their role can be especially important in plant development and adaptation to environmental conditions, probably by providing them with a fast mechanism to obtain complex and highly interconnected molecular networks [15]. It has been pointed out that several IDPs in plants play key roles in response to different stresses [10,11], in particular water stress [16,17,18]. It has been suggested that plants may use IDPs independently to adapt quickly and efficiently to environmental changes from which they cannot escape [10].…”
Section: Introductionmentioning
confidence: 99%
“…The origin of the thermal stability of eukaryotic proteins was studied and compared with that of thermophilic and mesophilic proteins of prokaryotes by Alvarez-Ponce et al The eukaryotic model system was Arabidopsis thaliana at 22 and 37 • C, and they compare both the amino acid compositions and levels of intrinsic disorder of heat-induced and heat-repressed proteins. Heat-induced proteins are enriched in intrinsically disordered regions and depleted in hydrophobic amino acids in contrast to thermophile prokaryotic proteins [15].…”
Section: Researchmentioning
confidence: 95%
“…The subcellular location was predicted as previously (Alvarez-Ponce et al, 2018), with minor modifications. For both defensins, the most likely subcellular location was retrieved from the SUBA4 database (Hooper et al, 2017) and compared with Phobius and SignalP predictions.…”
Section: Methodsmentioning
confidence: 99%